Burden and correlates of significant liver fibrosis among HIV-infected and uninfected adults in urban Uganda - Clara Wekesa; Ponsiano Ocama; Rosalind Parkes-Ratanshi; Gregory D. Kirk (Dialogues in Health, 2022)
Introduction: Following chronic inflammation and other disease specific factors, the risk of liver disease is believed to be higher among HIV-infected patients than in the general population despite shared risk factors. Understanding this differentiated burden and its drivers will inform policy and priority populations for intervention. Methods: This was a cross sectional study among 516 adults attending care clinics in Kampala Uganda. Significant liver fibrosis (SLF) was defined as liver stiffness measurement ≥7.2 KPa identified by Fibroscan®. Data analyses were stratified by HIV status and we performed logistic regression performed to identify correlates. Results: The prevalence of SLF was higher among HIV un-infected patients ((24% Vs 14%; p0.004). Overall HIV-uninfected patients were more likely to be overweight and or obese, with elevated serum cholesterol levels. Elevated measurement of fatty change in the liver (CAP scores >248 dB/m) was associated with SLF among HIV un-infected patients (OR 2.3 CI (1.0-5.2); p = 0.046). Low nadir CD4 counts (200cell/mm3) was predictive of SLF among HIV-infected patients (OR 3.3 CI (1.0-10.7); p = 0.05). Conclusion: The prevalence of SLF was unexpectedly higher among HIV un-infected than HIV affected patients attending care clinics in urban Uganda. This observed burden is most likely driven by non-alcoholic fatty liver disease (NAFLD) resulting from metabolic syndrome.